Health education interventions to promote early presentation and referral for women with symptoms of endometrial cancer - Chalong Cheewakriangkrai (2019)
© 2019 The Cochrane Collaboration. This is a protocol for a Cochrane Review (Intervention). The objectives are as follows: To determine the effectiveness of health education interventions involving healthcare providers or individuals or both to promote early presentation and early referral for women with symptoms of endometrial (womb) cancer.